2014
DOI: 10.1371/journal.pone.0107374
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Validating a Tablet Version of an Illness Explanatory Model Interview for a Public Health Survey in Pune, India

Abstract: BackgroundMobile electronic devices are replacing paper-based instruments and questionnaires for epidemiological and public health research. The elimination of a data-entry step after an interview is a notable advantage over paper, saving investigator time, decreasing the time lags in managing and analyzing data, and potentially improving the data quality by removing the error-prone data-entry step. Research has not yet provided adequate evidence, however, to substantiate the claim of fewer errors for computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 18 publications
3
39
1
1
Order By: Relevance
“…Our quantitative results on data quality are consistent with findings from other evaluations [3,6,7,10,11,1519]. On paper forms, the level of missing data increased with the complexity of skip patterns, while almost the opposite pattern was seen in EDC, showing the usefulness of programmed automatic skip patterns in guiding interviewers to the correct questions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our quantitative results on data quality are consistent with findings from other evaluations [3,6,7,10,11,1519]. On paper forms, the level of missing data increased with the complexity of skip patterns, while almost the opposite pattern was seen in EDC, showing the usefulness of programmed automatic skip patterns in guiding interviewers to the correct questions.…”
Section: Discussionsupporting
confidence: 89%
“…With a study size above a certain threshold (as start-up costs can be high), costs tend to be lower with EDC [6,7,10,13]. We were able to reduce costs in some areas, for example by buying devices in the UK, as they were expensive to buy locally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, a study with a similar design in India revealed with 2% PPDC and 1.99% EDC error rates [29]. However, this magnitude is lower compared to other similar studies (7% and 1%, with no omission in EDC) [9], 3.6% PPDC and 5.2% in EDC [33].…”
Section: Results In Relation To Other Studiesmentioning
confidence: 70%
“…Similar experience observed in a couple of recent studies [7,29]. The exact copy of the paper questionnaire converted to its electronic replica form using Excel and XLSForm.…”
Section: System Details and System In Usementioning
confidence: 83%